Rationale and design of a multicentre, 12-week, randomised, double-blind, placebo-controlled, parallel-group, investigator-initiated trial to investigate the efficacy and safety of elobixibat for chronic constipation. Issue 5 (30th May 2022) - Tanaka, Kosuke; Kessoku, Takaomi; Yamamoto, Atsushi; Takahashi, Kota; Kasai, Yuki; Ozaki, Anna; Iwaki, Michihiro; Kobayashi, Takashi; Yoshihara, Tsutomu; Misawa, Noboru; Kato, Takayuki; Arimoto, Jun; et al.
Abstract : Introduction: Chronic constipation (CC) is a functional disorder that negatively impacts the quality of life of patients. This is a protocol for a multicentre, 12-week, randomised, double-blind, placebo-controlled study to test the efficacy and safety of elobixibat (EXB) versus placebo in patients with CC. Methods and analysis: This will be a multicentre, double-blind, placebo-control, randomised controlled trial. A total of 100 adult patients with CC, diagnosed based on Rome IV criteria, who fulfil the inclusion/exclusion criteria will be enrolled. The patients will be randomly assigned to receive EXB (10 mg) or placebo treatment (n=50 per group). Blood tests and stool sampling will be performed 12 weeks following initiation of treatment and questionnaires will be issued to participants. The primary outcome will be the change in complete spontaneous bowel movements after 12 weeks of administration. The secondary outcomes will include the change in Japanese Patient Assessment of Constipation Quality of Life and absolute serum and faecal bile acid. Ethics and dissemination: Ethics approval has been obtained from Yokohama City University Certified Institutional Review Board before participant enrolment. The results of this study will be submitted for publication in international peer-reviewed journals and the key findings will be presented at international scientific conferences. Protocol version: V.3.0, 15 June 2021. Trial registration number: ClinicalTrials.gov (number NCT04784780 ).